Teacher Thinking and Professional Action. - Denicolo, Pam (Taylor & Francis Ltd., 2005)
Broad in theme, international in scope and thorough in detail, this book is based on a selection of papers presented at the third bi-annual ISATTs conference and updated by each contributor to include their current thoughts and opinions.